Koszty logistyki w systemie wskaźników efektywności procesów logistycznych - Piechota, Robert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The logistic processes provide many information and that is why one can observe growth of the need for introducing the modifications or development information systems in a sphere of needs of logistic controlling. It is very important to measure all results of logistic process activities, which should be pictured by quality and quantity data. The purpose of this paper is to underline the importance of modification and development information systems as the very important factors of effectiveness of logistic controlling. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1178, s. 116-122